The systematics of Neolycaena lunara Zhdanko, 1998 - complex of species (Lepidoptera: Lycaenidae) - Abdulaziz M. Davlatov (SHILAP, 2025)
The status and systematic position of the taxa of the Neolycaena lunara Zhdanko, 1998 group are discussed. It is shown that N. lunara has large variability in size, shape, and wing pattern parameters even within the same population. The following new synonymy is established: Neolycaena lunara oksana Korb, 2015, syn. nov., Neolycaena lunara karategina Weidenhoffer, 2000, syn. nov.